Immediate and short-term effect of physical exercise on BDNF in multiple sclerosis patients: a systematic review and meta-analysis - Andreu Caravaca, Luis (2025)
Low brain-derived neurotrophic factor (BDNF) concentrations have been found in individuals with multiple sclerosis (MS). Physical exercise is an effective strategy for acutely increasing the levels of this neurotrophin in various populations; nevertheless, definitive results are still required for individuals with MS. Thus, this systematic review with meta-analysis aimed to analyze the acute and short-term effects of physical exercise on BDNF concentrations in MS patients. In this pre-registered systematic review (PROSPERO; ID: CRD42024505920), six electronic databases (PubMed-Medline, Scopus, Web of Science, SportDiscus, EbscoHost, and Cochrane) were searched by two independent researchers to identify eligible studies investigating the acute or short-term effects (≤ 3 weeks) of physical exercise sessions on blood concentration of BDNF in MS. Studies that used a sample population with other pathologies or did not provide or specify numerical data on the specified variables were excluded. After applying the inclusion and exclusion criteria, nine studies were included. A total sample of 259 people with MS were analyzed. Effect sizes of outcomes were presented as standardized mean difference (SMD) and 95% confidence intervals (95%CI). The effect estimation was computed using the inverse variance random effects method. Immediately after a session, a significant increase in BDNF was observed (large standardized mean difference (SMD) = 1.52, p = 0.001, I2 = 95). A significant effect (SMD = 0.27, p = 0.05; I2=0%) was found after three weeks of physical training on the BDNF. Our study indicates that physical exercise is an appropriate stimulus to increase BDNF release in MS patients. The acute and short-term increases in this neurotrophin reflect physical exercise’s potential and interesting neuroprotective character in populations with neurodegenerative diseases.